The Role of Marketing Communications and Trust in Consumer Loyalty Shopee E-Commerce - Agus Yudianto; Bahtiar Efendi (Journal of Economics, Management, and Business, 2025)
Objective - This study aims to explain the application of marketing communication relationship strategies and customer trust towards customer loyalty in e-commerce. Method - Research This research method uses a causal quantitative method. Data analysis in the form of: data collection, data reduction, data presentation, and drawing conclusions. The data collection method uses questionnaires and document recording, which are analyzed using multiple regression, validity tests, and reliability tests. Results - The results show that the company carries out a marketing communication strategy by referring to integrated marketing communications by carrying out a strategy process in the form of: advertising, sales promotion, direct marketing, and public relations. With the strategy process carried out so far, it helps in increasing brand awareness of the wider community, improving the company's brand image, and increasing sales for the company and customer trust. Implications - Improving brand image and customer trust creates stronger long-term relationships with consumers. By creating a positive image through consistent communication, customers will be more loyal and more likely to make repeat purchases. Originality - applied by the company refers to a unique and innovative way of delivering marketing messages that differentiates the company from competitors in the market. This is related to the selection of approaches, channels, and ways of delivering messages that are not only interesting but also create a deep impression in the minds of consumers.